Industrial training report: FrieslandCampina Service Centre Asia Pacific - Mohd Misbah, Muhammad Faris (Universiti Teknologi MARA, Perlis, 2024)
An internship is a short-term work experience that companies offer to students or recent graduates with the goal of giving them real-world exposure in a particular industry. Internships often go from a few weeks to several months, and they can be full-time, part-time, paid, or unpaid. They help interns learn by letting them put their academic knowledge into practice, obtain practical experience, hone their professional abilities, and choose different career options. Interns gain significant networking opportunities, work under the guidance of seasoned professionals, and receive mentorship. In Malaysia, the industrial training program typically lasts three to six months to finish. My internship at FrieslandCampina Service Centre Asia Pacific, Petaling Jaya, Selangor, lasted six months (27 weeks), from March 5, 2024, to September 4, 2024. I have gained a great deal of experience and knowledge throughout my internship, particularly in the auditing profession, which I had not previously learned in my academic work. My boss, Miss Cecilia Suong, who oversees my Cash App team for FrieslandCampina, was in charge of me. Furthermore, I also have been given the chance to do a tax audit for our neighbouring country which is the Philippines. This experience can bring a lot of benefit to my knowledge and enhance my skill in using Microsoft Excel. Also, I can enhance my verbal communication skills in English due to the working environment. This internship experience has given me the opportunity to consider my professional options. I can determine whether a certain industry or work role fits with my interests and career ambitions thanks to the first-hand experience. This report began with my updated resume used to apply for an internship at FrieslandCampina Service Centre Asia Pacific. It includes my education, work experience, leadership roles, university achievements, and skills. I also provided an overview of FrieslandCampina, covering its background, vision, mission, objectives, organizational structure, and services. Additionally, I conducted a SWOT analysis, identifying two findings for each component: strengths, weaknesses, opportunities, and threats. Overall, I found that practical training at a company service centre offers a comprehensive learning experience, bridging theoretical knowledge with real-world application and preparing me for a career in auditing and accounting.